Crab Mentality: Penyakit Mental Interaksi Sosial - Indriyani; Nur Endah Safitri; Yulius Dani Nugraha (Yayasan Aya Sophia Indonesia, 2023)
The purpose of this study is to find out the perspective of the knowledgeable YouTube channel entitled